Intervensi Sisi Lingkungan dan Kemampuan Belanja Makanan Berpengaruh Untuk Menurunkan Keluhan Kesehatan - Retnaningsih, Ekowati; Maryani, Sri; Sihombing, Pardomuan Robinson; Nuryanto, Nuryanto (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2024)
Clean water and proper sanitation are basic human needs that are one of the goals of sustainable development. Poor environmental sanitation will also adversely affect health. The purpose of this study was to determine the effect of environmental health determinants and expenditure on food on health complaints. The research method is a longitudinal survey, using aggregate data from SUSENAS, panel data from 34 Provinces in Indonesia for the 2018-2022 period. Data processing using STATA. The results found that three significant variables influenced health complaints, namely sanitation, access to drinking water and per capita food expenditure. The results found that three significant variables influenced health complaints, namely sanitation access variables, access to drinking water and per capita food expenditure. The most influential variable is per capita food expenditure. It was concluded that to reduce health complaints, interventions are needed to increase access to environmental health and increase expenditure on food as a basis for increasing adequate nutritional consumption.